Sustainable biodiesel production from microalgae cultivated in wastewater treatment ponds - Brar, Prabhdeep Kaur (My University, 2024)
Microalgae-based biodiesel production has emerged as a promising avenue for renewable and sustainable energy sources. This thesis presents a comprehensive analysis of the technical feasibility and sustainability of microalgae-derived biodiesel production, focusing on cultivating indigenous mixed species in wastewater collected from rural oxidation ponds. Furthermore, a bi-functional KOH/rice bran-derived activated heterogeneous carbon catalyst was employed for the in-situ transesterification process and process parameters were utilized using statistical regression analysis by central composite design (CCD). The study includes microalgae cultivation sourced from a rural pond, providing a lab-scale demonstration of logistic growth patterns over two weeks. This approach showcases the potential to utilize wastewater as a growth medium, eliminating the need for additional nutrient supplementation and reducing freshwater consumption. Chlorophyll-A in wastewater confirms the presence of microalgae, setting the stage for a sustainable biomass source. A pivotal aspect of the research involves identifying and characterizing indigenous microalgae species. Morphological observations under the microscope provide valuable visual clues, while molecular techniques, including 16S rRNA gene sequencing and BLASTN searches, confirm the genetic identity of the strains as Desertifilum salkalinema and Chlorella vulgaris. Developing a novel bi-functional catalyst consisting of KOH impregnated on rice bran-derived activated carbon support material represents a significant milestone. Characterized through scanning electron microscopy (SEM) and X-ray diffraction (XRD), this catalyst enhanced the efficiency of in situ transesterification by effectively filling porous structures. Exploration of solvent combinations for direct transesterification with synthesized catalyst was carried out. In-situ transesterification with H2SO4 was carried out to find the most suitable vi combination. The successful identification of methanol and hexane as the optimal solvent duo maximized the efficiency of the direct transesterification process with the synthesized catalyst. Optimization of process parameters was achieved through statistical regression analysis based on the central composite design (CCD). The model generated from this analysis predicts a biodiesel yield of 81.8%, with a high coefficient of determination (R² = 0.94), ensuring the model's reliability. The optimum conditions include a 10:1 solvent and co-solvent to biomass molar ratio, 5 wt% catalyst loading, a temperature of 70°C, and a 1.5-hour reaction time. In practice, these conditions yielded an observed maximum biodiesel yield of 80.9%, with a prediction error below 0.9%. Furthermore, characterization of the obtained biodiesel through gas chromatography–mass spectrometry (GC–MS) analysis revealed a composition containing 53.82% unsaturated fatty acids, making it suitable for extreme weather conditions. Additionally, all biodiesel properties met American Society for Testing and Materials (ASTM) standards, ensuring compliance with industry-scale quality requirements. In conclusion, this research advances the field of microalgae-based biodiesel production by optimizing the production process, utilizing indigenous mixed microalgae species, and developing an innovative bi-functional catalyst. The findings underscore microalgae-derived biodiesel's technical feasibility and sustainability, positioning it as a cost-effective, green, and renewable energy source with significant potential in the renewable energy sector.
Keywords: Microalgae biodiesel; indigenous microalgae species, KOH/rice bran-derived bio-based catalyst, direct transesterification, central composite design, process optimization